Gun Violence and Risk to Children and Youth in the United States. Issue 3 (May 2023) - Simpson, Kathleen Rice; Rohan, Annie J.
Abstract : Nurses interact with children, youth, and their families routinely and have been widely acknowledged as the most trusted professionals for over 20 years. Nurses can use this trust relationship to encourage parents to practice gun safety as outlined by the American Academy of Pediatrics. Nurses should advocate for gun safety legislation on the local, state, and national level. Nurses must do all that they can to keep America's children and youth safe from gun violence.